Fall Prevention in Community Settings: Results from Implementing Stepping On in Three States - Ory, Marcia G.; Smith, Matthew Lee; Jiang, Luohua; Lee, Robin; Chen, Shuai; Wilson, Ashley D.; Stevens, Judy A.; Parker, Erin M. (Frontiers in Public Health, 2015)
Stepping On is a community-based intervention that has been shown in a randomized controlled trial to reduce fall risk. The Wisconsin Institute for Healthy Aging adapted Stepping On for use in the United States and developed a training infrastructure to enable dissemination. The purpose of this study is to: (1) describe the personal characteristics of Stepping On participants; (2) quantify participants’ functional and self-reported health status at enrollment, and (3) measure changes in participants’ functional and self-reported health status after completing the program. Both survey and observed functional status [timed up and go (TUG) test] data were collected between September 2011 and December 2013 for 366 participants enrolled in 32 Stepping On programs delivered in Colorado, New York, and Oregon. Paired t-tests and general estimating equations models adjusted for socio-demographic factors were performed to assess changes over the program period. Among the 266 participants with pre–post survey data, the average participant age was 78.7 (SD ± 8.0) years. Most participants were female (83.4%), white (96.9%), and in good health (49.4%). The TUG test scores decreased significantly (p < 0.001) for all 254 participants with pre–post data. The change was most noticeable among high risk participants where TUG time decreased from 17.6 to 14.4 s. The adjusted odds ratio of feeling confident about keeping from falling was more than three times greater after completing Stepping On. Further, the adjusted odds ratios of reporting “no difficulty” for getting out of a straight back chair increased by 89%. Intended for older adults who have fallen in the past or are afraid of falling, Stepping On has the potential to reduce the frequency and burden of older adult falls.